2022
DOI: 10.3390/metabo12070611
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Children with Autism Spectrum Disorders: Determinants and Effects of the Response to Probiotic Supplementation

Abstract: A relationship between the presence of clinical symptoms and gastrointestinal (GI) disturbances associated with nutritional deficiencies, including vitamin D (25(OH)D) deficiency, has been observed in autism spectrum disorder (ASD). The aim was to evaluate 25(OH)D levels according to the annual rhythm cycle, gender, the severity of autism, nutritional or clinical status, inflammatory and metabolic biomarkers, GI symptoms, and the clinical response to probiotic/placebo supplementation in preschooler children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…First reports on the possibility of using vitamin D to treat autism originate from 2014 when vitamin D was administered intramuscularly and orally to a three-yearold boy with ASD. A significant improvement in his health was noticed after increasing the vitamin level [5,22]. Further research has shown that vitamin D supplementation may relieve ASD symptoms [15] in about 75% of autistic children.…”
Section: State Of the Knowledgementioning
confidence: 95%
See 2 more Smart Citations
“…First reports on the possibility of using vitamin D to treat autism originate from 2014 when vitamin D was administered intramuscularly and orally to a three-yearold boy with ASD. A significant improvement in his health was noticed after increasing the vitamin level [5,22]. Further research has shown that vitamin D supplementation may relieve ASD symptoms [15] in about 75% of autistic children.…”
Section: State Of the Knowledgementioning
confidence: 95%
“…A relationship between the neurological symptoms and gastrointestinal problems associated with nutritional deficiencies, including (25(OH)D) deficiency, has been frequently frequently observed in ASD in the scientific literature. [22].…”
Section: State Of the Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have linked ASD to Vitamin D deficiency during pregnancy and early childhood 12,13,39 . The underlying molecular mechanisms remain poorly understood, but a key role for neurotransmitter metabolism has been recently suggested 13,39 .…”
Section: Reconstructing Patient-specific Metabolic Network Through Li...mentioning
confidence: 99%
“…Metaanalyses have also identified a series of environmental risk factors, including pre-natal, perinatal, and post-natal elements 5,6,10 . Among these factors, vitamin D has been increasingly implicated in ASD pathogenesis [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%